A new gamboge derivative Compound 2 inhibits cancer stem‐like cells via suppressing EGFR tyrosine phosphorylation in head and neck squamous cell carcinoma. Issue 11 (23rd September 2013) - Deng, Rongxin; Wang, Xu; Liu, Yang; Yan, Ming; Hanada, Sayaka; Xu, Qin; Zhang, Jianjun; Han, Zeguang; Chen, Wantao; Zhang, Ping
Abstract Cancer stem‐like cells represent a population of tumour‐initiating cells that lead to the relapse and metastasis of cancer. Conventional anti‐cancer therapeutic drugs are usually ineffective in eliminating the cancer stem‐like cells. Therefore, new drugs or therapeutic methods effectively targeting cancer stem‐like cells are in urgent need to successfully cure cancer. Gamboge is a natural anti‐cancer medicine whose pharmacological effects are different from those of conventional chemotherapeutical drugs and they can kill some kinds of cancer cells selectively. In this study, we identified a new gamboge derivative, Compound 2 (C2), which presents eminent suppression effects on cancer cells. Interestingly, when compared with cisplatin (CDDP), C2 effectively suppresses the growth of both cancer stem‐like cells and non‐cancer stem‐like cells derived from head and neck squamous cell carcinoma (HNSCC), inhibiting the formation of tumour spheres and colony in vitro, resulting in the loss of expression of multiple cancer stem cell (CSC)‐related molecules in HNSCC. Treating with C2 effectively inhibited the growth of HNSCC in BALB/C nude mice. Further investigation found that C2 notably inhibits the activation of epithelial growth factor receptor and the phosphorylation of its downstream protein kinase homo sapiens v‐akt murine thymoma viral oncogene homolog (AKT) in HNSCC, resulting in down‐regulation of multiple CSC‐related molecules in HNSCC. Our study has demonstrated that C2 effectively inhibits the stem‐like property of cancer stem‐like cells in HNSCC and may be a hopeful targeting drug in cancer therapy.